Analisis Pengaruh Arus Kas terhadap Kinerja Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Rizal Tomu; Longginus Gelatan (Journal of Financial and Tax, 2023)
This study aims to determine the effect of cash flow from operating activities, investment activities, and funding activities on the performance of banking companies listed on the Indonesia Stock Exchange. This study used associative methods with a quantitative approach with data collection techniques using documentation. The data analysis instrument used is multiple linear regression analysis to measure the effect of cash flow from operating activities, investment activities, and funding activities on the performance of banking companies listed on the Indonesia Stock Exchange. The results of the analysis show that cash flow of operating activities has a significant effect on the performance of banking companies while cash flow of investment activities has a significant effect on the performance of banking companies and cash flow of funding activities has no effect but is significant on the performance of banking companies